DENSITAS HAMA BIBIT TANAMAN HUTAN DI PERSEMAIAN PERMANEN BPDASHL WAY SEPUTIH WAY SEKAMPUNG LAMPUNG SELATAN - Yolanda Ayu Saputri; Indriyanto Indriyanto; Ceng Asmarahman (Jurnal Belantara, 2023)
The density of pest attacks in nurseries can interfere with growth and reduce seedling quality and can even cause death and cause economic losses. This study aims to analyze the density of each type of pest in the nursery. Data collection was carried out by direct observation of the sample plot at the BPDASHL Way Seputih Way Sekampung Permanent Nursery, Karang Sari Village, Ketapang District, South Lampung Regency. The sample was determined by Cluster Sampling which was based on the type of tree seed, while the placement of sample plots in each seedling bed used Systematic Sampling. The results showed that there were 19 types of pests that attack forest plant seeds in nurseries including leaf curler caterpillars, armyworms, bagworms, brown moths, wood grasshoppers, stone grasshoppers, green steamed grasshoppers, two-lane grasshoppers, small grasshoppers, dompolan lice, lamtoro lice , metallic blue beetle, red rumex beetle, sitona beetle, triple horn moth, walang sangit, koksi beetle, stem borer and snail. The highest density of pests that attack forest seedlings are wood locusts, stem borer beetles and dompolan lice. Nurseries need to monitor the development of pest populations and maintain a balance of climate and cleanliness of the area around the nursery with appropriate silvicultural measures.